Continued health education: challenges for management in public health - Eduarda Signor; Luiz Anildo Anacleto da Silva; Iris Elizabete Messa Gomes; Rodrigo Verzeletti Ribeiro; Marciane Kessler; Teresinha Heck Weiller; Anahlú Peserico (Universidade Federal de Santa Maria, 2015)
Aim: to understand what the challenges for continued health education are in a city in the north of Rio Grande do Sul, which corresponds to the area of the 15th Regional Health Care Coordination. Method: descriptive and exploratory research, with qualitative approach. The data collection was carried out in august 2013. Content analysis was used for the data interpretation. The study subjects were 17 employees of the multidisciplinary team of urgency and emergency care. Results: the data of the study enabled the development of two categories: the first, "Challenges in educational strategies focused on workers", and the second, "Challenges in educational strategies designed to the users." It is highlighted that the activities of Continued Health Education are insufficient and inadequate. Conclusion: the study shows the necessity and relevance to develop activities with this approach. Furthermore, it is essential that managers are committed in order to carry them out